Quantum Codes from a Class of Constacyclic Codes over Group Algebras - Koroglu, M. E.; Siap, I (UNIV PUTRA MALAYSIA PRESS, 2017)
In this work, we determine self dual and self orthogonal codes arising from constacyclic codes over group algebras. Also, based on these codes we obtain some good parameters for quantum error-correcting codes.
Keywords: Group algebras; constacylic codes; linear codes; quantum codes; MDS CODES; Mathematics